The impact of statin therapy and aerobic exercise training on skeletal muscle and whole-body aerobic capacity - Jill M. Slade; George S. Abela; Mitchell Rozman; Robert J. McClowry; David Hurley; Sean C. Forbes; Ronald A. Meyer (American Heart Journal Plus, 2021)
Background: Statin use is widely recognized for improving cardiovascular health, but questions remain on how statin use influences skeletal muscle, particularly mitochondrial function. Study objective, design and participants: The influence of statin therapy and exercise (EX) on aerobic capacity was determined. In Study1, skeletal muscle aerobic capacity was measured before and after 80 mg atorvastatin therapy. In Study2, aerobic capacity (skeletal muscle and whole body) was measured before and after a 12-week exercise randomized control trial in older adults (age = 67 ± 5 yrs.), a subset of which were on chronic low-moderate intensity statin therapy. Main outcome measures: Muscle oxidative capacity was determined from the phosphocreatine recovery rate constant (kPCr) using 31P Magnetic Resonance Spectroscopy. Whole body peak oxygen uptake (VO2 peak) was measured during a graded exercise test with indirect calorimetry. Results: High dose statin therapy resulted in a 12% reduction in muscle oxidative capacity (pre = 1.34 ± 0.34 min−1, post = 1.17 ± 0.25 min−1, p = 0.004). Similarly, chronic low-moderate dose statin therapy was associated with lower muscle oxidative capacity at baseline (1.50 ± 0.35 min−1) compared to non-statin users (1.88 ± 0.047 min−1, p = 0.019). Following EX, muscle oxidative capacity increased by 35–40% (statin: Pre: 1.39 ± 0.44 vs. Post: 1.88 ± 0.47 min−1, no statin Pre: 1.86 ± 0.58 vs. Post: 2.58 ± 0.85 min−1) compared to control groups (Pre: 1.74 ± 0.27 vs Post: 1.75 ± 0.49 min−1, p = 0.001). VO2 peak increased by 11% for EX groups (Pre: 18.8 ± 2.8 vs. Post: 20.8 ± 3.0 ml·kg−1·min−1) following training compared to a small decline in controls (Pre: 21.8 ± 3.7 vs. Post: 20.8 ± 3.04 ml·kg−1·min−1, p = 0.001). Conclusions: Statin therapy resulted in reduced muscle oxidative capacity. Aerobic exercise improved skeletal muscle oxidative capacity and whole-body aerobic capacity during statin therapy.